2006
DOI: 10.1111/j.1532-5415.2005.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Geriatric Medical Student Scholars Program: A Qualitative Assessment

Abstract: In 2003, the University of Cincinnati College of Medicine initiated a 4-year Geriatric Medical Student Scholars (GMSS) program in which a selected group of 14 medical students participated in a variety of extracurricular geriatrics-related activities such as one-on-one mentoring and discussion groups. These students were also required to compose journal entries describing GMSS program-related activities using a semistructured on-line computer program designed specifically for this purpose. The reflective journ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…22,23 Active reflection on the meaning of events encountered during training helps trainees become critical thinkers. 24,25 Each scholar was asked to submit 6 journal entries using a semistructured guide to help them focus on their experiences abroad (T A B L E 1 ).…”
Section: Didactic Curriculum and Lecturesmentioning
confidence: 99%
“…22,23 Active reflection on the meaning of events encountered during training helps trainees become critical thinkers. 24,25 Each scholar was asked to submit 6 journal entries using a semistructured guide to help them focus on their experiences abroad (T A B L E 1 ).…”
Section: Didactic Curriculum and Lecturesmentioning
confidence: 99%
“…• Aprendizaje de los principios éticos y otros aspectos difíciles de enseñar con métodos tradicionales (27,40).…”
Section: Beneficios Del Uso Del Diariounclassified
“…Por tanto, es indispensable la creación de un ambiente de confianza en el que el estudiante pueda escribir de forma honesta y sin temor a represalias (2,9,24,33,36,47). En las prácticas clínicas de enfermería se describen aspectos con mucha carga emocional, que podrían omitirse en el diario por falta de confianza con el profesor (26,39,40).…”
Section: Beneficios Del Uso Del Diariounclassified
See 1 more Smart Citation
“…Goldenhar and Kues (2006) conducted a study at the University of Cincinnati College of Medicine that required students in the Geriatric Medical Student Scholars program to journal about their practices. The results showed that reflective writing provided both personal and professional learning.…”
Section: Reflective Writing and Reflective Practice In Clinicalmentioning
confidence: 99%